THE ROLE OF ONLINE ENGLISH COMMUNITY DURING COVID-19 PANDEMIC - Siti Hadianti; Bobi Arisandi (Universitas Islam Sumatera Utara (UISU), 2020)
The outbreak of coronavirus disease 2019 (COVID-19) has caused many new challenges for educational institutions. Most schools and universities have been transforming the learning mode into an online platform and it leaves teachers and students in a challenging situation. The existence of English community which helped to provide exposure and practice toward English learning is postponed due to COVID-19 pandemic. Online English community as an alternative to replace English community has not been observed well before. Its flexibility in learning is assumed that it can enhance a better engagement in the English learning activity. The purpose of this study is to investigate the role of the online English community during COVID-19 pandemic. Fifteen university students that are involved in one online English community participated in the research. The researchers chose the sample by using purposive sampling. The data was collected through questionnaire and interview and the method that is used is qualitative research with a case study design. The researchers found that there are at least 3 roles of online English community during COVID-19 pandemic.